(untitled) (Research, Society and Development, 2021)
Even though the problems of education in Brazil are known, the pandemic caused by Covid-19 has surfaced discussions in different areas and intense mobilizations for the continuity of the educational process. The present study is a qualitative research that aims to analyze and present data obtained through research carried out with teachers in order to map the strategies, challenges and lessons of remote education experienced in this period of necessary social distancing. For data collection, an electronic questionnaire was used, with the participation of professors working in public and private educational institutions in several Brazilian regions. The non-probabilistic sampling method called Virtual Snowball (or sample by network) was used, which consisted of sending the questionnaire through a link, by email and WhatsApp, containing the questions, the Informed Consent Form and Clarified - Virtual IC and the request to share the link with that participant’s network of contacts. The study showed that, although there are different realities of action and some cases of success, there were points consensual as compromising the pedagogical practice and the learning process, such as difficulties in accessing technological resources and the internet for students, non-development autonomy for learning, the difficulty of monitoring parents/guardians, excessive activities by both educators and parents, the content of the school system, and the negative effects on the mental health of everyone involved in the system.